Comparative study of pharmacokinetics and serum bactericidal activity of ceftizoxime and cefotaxime. - Vallée, F (1991)
Single 2-g intravenous doses of ceftizoxime (CZX) and cefotaxime (CTX) were given over 30 min to 10 adult volunteers in a crossover manner on two separate occasions. Concentrations of CZX, CTX, and the primary metabolite of CTX, desacetylcefotaxime (dCTX), in serum, suction-induced-blister fluid, and urine were determined by high-pressure liquid chromatography. Pharmacokinetic parameters were estimated by using an extended least-squares modeling program (MKMODEL). CZX exhibited a half-life in serum (2.05 h) longer than that of CTX (1.43 h) but comparable to that of dCTX (2.02 h). The percentage of penetration in blister fluid, estimated by area under the curve ratios, was significantly higher for CZX (164.4%) than for CTX (60.8%). Serum bactericidal activity, determined for volunteer samples at 1, 6, 8, and 12 h after patients were dosed, against clinical isolates of the Bacteroides fragilis group, Enterobacter cloacae, Escherichia coli, Klebsiella pneumoniae, and Morganella morganii were significantly higher for CZX than those for CTX against members of the family Enterobacteriaceae at all times. Serum bactericidal titers against B. fragilis were also higher for CZX than for CTX at 1 h postinfusion. Neither CZX nor CTX exhibited any bactericidal activity at any other time against the B. fragilis group. In conclusion, the serum bactericidal activity of CZX was greater and more-prolonged than that of CTX against tested strains in spite of the in vitro synergistic contribution of dCTX to CTX, equal serum elimination half-lives of dCTX and CZX, and similar antibacterial activity and similar instability under microbiological testing for CZX and CTX.